Disease burden of the most commonly detected respiratory viruses in hospitalized patients calculated using the disability adjusted life year (DALY) model - Gaunt, E.R. (J Clin Virol, 2011)
BACKGROUND: The most common acute infections occur in the respiratory tract. Recent discoveries of several novel viruses have markedly increased the repertoire of agents understood to cause presentations of acute respiratory disease. OBJECTIVES: Further understanding is needed of the relative importance of newly discovered pathogens in the clinical setting to provide clinicians with an indication of appropriate diagnostic and therapeutic targets. To address this, quantification of the disease burden of respiratory viruses in hospitalized patients was undertaken. STUDY DESIGN: Disease burden caused by respiratory viruses in hospitalized patients was quantified using the World Health Organization endorsed DALY model. Diagnostic testing results from samples collected over three years for adenovirus (AdV), influenzas A and B, parainfluenza viruses 1, 2 and 3 (PIV-1, -2 and -3), respiratory syncytial virus (HRSV), and previously published retrospective screening for human metapneumovirus, rhinoviruses, and four respiratory coronaviruses were applied to the DALY model. Disability weights were calculated per 1000 hospitalized patients in age banded groups. RESULTS: Strikingly different disease burden profiles were observed in children and adults. Adenoviruses were among the leading cause of respiratory presentations in children but not adults. HRSV and influenza A were consistently one of the greatest causes of disease regardless of sampled population. Rhinoviruses and PIV-3 were significant pathogens in all groups except those aged 16–64 years. In immunocompromised patients rhinoviruses were the leading viral cause of disease. CONCLUSIONS: These analyses provide a framework which can be used to identify where finite resources should be directed in respiratory therapeutics and vaccine development.